A identidade da personagem Mariano no romance um rio chamado tempo, uma casa chamada terra, de mia couto. - Freitas, Vanessa Stephany Silva Pinheiro (Universidade Federal do Tocantins, 2022)
This work analyzes the identity of the character Mariano in the novel Um rio chamado tempo, uma casa chamada terra, written by the author Mia Couto (2003). It aims to discuss about the identity transformations experienced by the protagonist, mediated by the memory element in his return to the Luar-do-Chão. This bibliographic research, associated with the narrative analysis, sustained by the theorists such as Stuart Hall (2006; 2003) and Anthony Giddens (2002), who dialogue about the identity theme, considering the post-modernity context. Was selected excerpts from the novel, highlighting aspects that evidence a fragmentation in the identity of the character. Then, from the data analysis, became illusory to think that the identity as being pure, fixed, and stable, since it constitutes a multiple factor in a formation. Identity has a transitory character, the post-modern subject tends to assume multiple identification possibilities, subject to modifications, according to the social context in which it is inserted.